1998
DOI: 10.1152/ajpregu.1998.274.3.r577
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor in the heart

Abstract: The heart is a tumor necrosis factor (TNF)-producing organ. Both myocardial macrophages and cardiac myocytes themselves synthesize TNF. Accumulating evidence indicates that myocardial TNF is an autocrine contributor to myocardial dysfunction and cardiomyocyte death in ischemia-reperfusion injury, sepsis, chronic heart failure, viral myocarditis, and cardiac allograft rejection. Indeed, locally (vs. systemically) produced TNF contributes to postischemic myocardial dysfunction via direct depression of contractil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
587
3
13

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(620 citation statements)
references
References 286 publications
(340 reference statements)
17
587
3
13
Order By: Relevance
“…This cardiac inflammation is linked with decreased LV function, not only in diabetic cardiomyopathy, but also for example in myocardial infarction, pressure overload, and dilated cardiomyopathy [20][21][22]. Increased cytokines are one of the mechanisms leading to LV dysfunction in diabetes mellitus, as demonstrated by an inverse correlation between dP/dt max and TNF-α in diabetic animals in this study.…”
Section: Cardiac Inflammationsupporting
confidence: 58%
“…This cardiac inflammation is linked with decreased LV function, not only in diabetic cardiomyopathy, but also for example in myocardial infarction, pressure overload, and dilated cardiomyopathy [20][21][22]. Increased cytokines are one of the mechanisms leading to LV dysfunction in diabetes mellitus, as demonstrated by an inverse correlation between dP/dt max and TNF-α in diabetic animals in this study.…”
Section: Cardiac Inflammationsupporting
confidence: 58%
“…We found that, in the absence of extracellular Ca 2ϩ , cardiomyocytes maintained a normal rod-shaped morphology; however, the addition of extracellular Ca 2ϩ resulted in a loss of viability as indicated by rounding of the cells, which was markedly accelerated in cells with increased TRPC3 expression. In contrast, TRPC3 overexpression had no effect on the response of cardiomyocytes to TNF-␣, which induces apoptosis via a Ca 2ϩ -independent pathway by means of the TNF type-1 receptor and Fas activation (22) (Fig. 7).…”
Section: Discussionmentioning
confidence: 96%
“…Adiponectin belongs to an adipokine superfamily. Another adipokine, TNFα, is also expressed and secreted from cardiomyocytes [27]. Interestingly, the globular domain of adiponectin displays highly similar homo-trimeric three-dimensional structures to that of TNFα, even though they have unrelated amino-acid sequences [28].…”
Section: Discussionmentioning
confidence: 99%